Indications of Primary Caesarean Section in Multipara Patient (The Planet, 2022)
Background: It's believed that if a mother's first kid is born vaginally, subsequent births will be the same. As a result, multiparous moms typically ignore standard prenatal checkups and intranatal care, which can cause poor birth outcomes. Analysis of the Caesarean section (CS) in women with previous vaginal birth. Objective: To analyze the indications of primary caesarean section inmulti para women. Methods: The present cross-sectional study was conducted in the Department of Obstetrics & Gynaecology, Chittagong Medical College & Hospital, Chittagong between July 2016 to June 2017. During this period 150 multipara women were selected as study population from total admitted patients. Results: The individuals' ages ranged from 19 to 45 years (mean: 28.7+_5.6). 86% of patients were Muslim, 14% were other ethnicities. Nearly 25% of women were upper-class, 54% middle-class, and 21.3% lower-class. 35% of moms had regular ANC, 48% irregular, and 17.3% none. The patients were 80% multipara and 20% grandmultipara. 78% were hospitalized at term, 16.7% at preterm, and 5.3% postterm. Out of 150 patients, 18 (12%) had APH, 11.3% had preeclampsia (PE), 6.7% oligohydramnion, 5.3% polyhydramnion, 4.7% IUGR, 5.3% postterm pregnancy, and 1.3% HELLP syndrome. 35.3% of patients had anemia, 4.7% diabetes, 6% UTI, 3.3% chronic hypertension, and 0.7% asthma. Over 25.3% of pregnant women were blood group A, 27.4% B, 11.3% AB, and 36.3% O. 93.3% were Rh-positive. Foetal distress (24.7%) and prolonged 1st stage of labour (25%) were the main indications for caesarean section, followed by placenta praevia (16%),obstructed labour (14%), pre-eclampsia (13.3%), BOH (10.7%), malpresentation (9.3%), transverse lie (6%), eclampsia (2%) and previous VVF repair (0.7%)and others (3.3 percent). 4.7 hours passed between caesarean decision and delivery. 126 (84%) moms had emergency surgery; 24 (16%) had elective surgery. 15% of women experienced significant bleeding and 2% anesthetic complications. Postoperative wound infection was 14%, followed by failure of lactation (11.3%), post spinal headache (7.3%), PPH (6%), UTI (4.7%), urine retention (4%), and postpartum eclampsia (0.7%). 12 births (8%) had perinatal death among them 8(66.7%) had stillbirths and 3(33.3%) neonatal deaths. 34.7% of newborns required resuscitation. About 20% of newborns were low-birth-weight, 75.3% were normal, and 5.1% were overweight. 42% of newborns had APGAR
Keywords: Multipara patients; Caesarean section; Indications of CS; Outcome